Sebaran Pelayanan Kesehatan Penderita Hipertensi Di Kabupaten Kupang Tahun 2020 Dengan Aplikasi QGis - Yersintha Katarina; Yendris Krisno Syamruth (Jurnal Kesehatan, 2022)
Hypertension is one of the non-communicable diseases that causes almost 70% of deaths in the world and continues to increase every year. This study aims to analyze the areas with the highest prevalence of hypertension sufferers at risk for disease control and improvement of health services through mapping using the QGis application. This type of research is a research with secondary data analysis approach. This research method begins with data collection at the Kupang District Health Office, data preprocessing and mapping with the QGis application. The results showed that the number of hypertensive patients who received health services according to the highest sub-district was in the East Kupang sub-district, which was 1124 patients and the lowest was in the Southwest Amfoang sub-district, which was 108 patients. It is expected that the Kupang City Health Office can make disease reports in the form of mapping using the Qgis application so that it can facilitate the presentation of data to determine the coverage of patients receiving health services in Kupang Regency.